The Potential of Young Coconut Fiber as an Organic Dye and Its Applications on Silk Thread - Neliyarti Neliyarti; Eri Barlian; Abdul Razak; Nurhasan Syah; Heldi Heldi; Muhamad Sholichin (Jurnal Penelitian Pendidikan IPA, 2025)
Young coconut fibers, often found as waste, contain tannin and anthocyanin compounds that can produce various natural colors, so they can be used as organic dyes. The research method used was an experiment with a focus on testing silk thread dyeing using young coconut fiber extract dissolved in rice field water. This study aims to explore and develop the use of young coconut fibers as a source of environmentally friendly natural dyes. The results showed that young coconut fibers have the potential as organic dyes. Young coconut fiber extract with fermented rice field water solvents produced three color variations depending on the fixator used: brownish black (ferrous sulfate), gray (alum), and brown (lime). Structural tests using Scanning Electron Microscopy (SEM) proved that the dyeing process did not change the cross-sectional shape of the silk thread. In terms of tensile strength, yarn with alum fixation had the highest strength compared to native yarn, ferrous sulfate fixation, and lime fixation. Elongation tests showed the highest elasticity in yarn with alum fixation, followed by lime, ferrous sulfate, and native yarn. The color fastness test against washing at a temperature of 40°C showed a fairly good level of fastness for organic dyes from young coconut fiber